Growth and characterization of ultrathin carbon films on electrodeposited Cu and Ni. (1st August 2017) - Pedrazzetti, L.; Nobili, L.; Magagnin, L.; Bernasconi, R.; Lucotti, A.; Soltani, P.; Mezzi, A.; Kaciulis, S.
Abstract: Ultrathin carbon films were grown on different types of metallic substrates. Free‐standing foils of Cu and Ni were prepared by electroforming, and a pure Ni film was obtained by galvanic displacement on a Si wafer. Commercial foil of Ni 99.95% was used as a reference substrate. Carbon films were grown on these substrates by chemical vapour deposition in a CH4 ‐H2 atmosphere. Obtained films were characterized by Raman spectroscopy, X‐ray photoelectron spectroscopy (XPS), Auger electron spectroscopy, and ultraviolet photoemission spectroscopy. The XPS at grazing collection angle was used to determine the thickness of carbon films. Depending on the deposition parameters, the films of graphene or graphite were obtained on the different substrates. The uniformity of graphene and its distribution over the sample area were investigated from Raman data, optical images, and XPS chemical maps. The presence of graphene or graphite in the films was determined from the Raman spectra and Auger peak of C KVV. For this purpose, the D parameter, which is a fingerprint of carbon allotropes, was determined from C KVV spectra acquired by using X‐rays and electron beam. A formation of an intermediate layer of metal hydroxide was revealed in the samples with graphene overlayer.